RELATIONSHIP BETWEEN ENVIRONMENTAL PERFORMANCE OF CHAIN IN HOTELING INDUSTRY AND GREEN HRM - Umar Farooq; Usman Nasir; Iftikhar Hussain; Atif Butt; Raja Faheem Shoukat (International Journal of Contemporary Issues in Social Sciences, 2024)
With COVID-19 limitations in place worldwide, the topic of "Relationship of Green Human Resources and Environmental Performance of chain in Hoteling industry" is still relatively fresh and unique. Using self-actualization, family-supportive behavior, and green human resources management, this study will improve the chain’s environmental performance and green human resources in the hotel business. The results demonstrate "that eco-friendly behavior, GHRM practices, and environmental performance of chain in hoteling business are improved by green human resource management.” The present study suggests that the use of GHRM techniques can improve the environmental performance of hotel chains.